The utility of corporate governance in managing financial risks in banks -case study of a local bank- - BOUKEFFA , Hamza (Journal of Research in Finance and Accounting, 2022)
This article provides a comprehensive overview of topics focusing on corporate governance and the assessment, analysis, and management of financial risks in banking. It emphasizes risk management principles and stresses that key players in the corporate governance process are accountable for managing the different dimensions of financial and other risks. In this sense, the first section presents a review of literature concerning the concept of corporate governance and financial risks management. The second section will be dedicated to the empirical study, from which we have learnt that there is a significant importance of corporate governance in enhancing financial risks management in banks.